Three essais in structural change economics - (:unkn) unknown (My University, 2022)
This thesis addresses three aspects of structural change. The first chapter focuses on the opportunities and constraints of demographic dynamics for agricultural modernization in different regions of the world. We are particularly interested in the African continent. We found that these dynamics have contradictory impacts on agricultural mechanization. Urban population growth is increasing local demand for food and encouraging investment in machinery. However, rural population growth is tempering this effect by increasing the number of suppliers, decreasing the average farm size, and supplying farms with a lower-cost alternative to machines: farm labor. The second chapter analyzes the industrialization process of three historically `comparable' countries: Morocco, Malaysia, and South Korea during the second half of the XXth century. First, we analyze the industrial policies pursued in these three countries and the social and political conditions of their adoption. Then we study the effect of these policies on accumulation, growth, distribution, and structural change. At the end of the chapter, we propose an analytical framework to guide future research for a theory of industrialization. Morocco's industrial policy, in its latest version, abandons the idea of a Moroccan industry in favor of an industry made in Morocco by foreign capital. While the macroeconomic effects of this policy are commendable on production, employment, and exports, its effects on local firms are not known. Economic theory promises knowledge externalities to the benefit of local firms. Our empirical study only finds negative effects of competition that operates at several levels.
Keywords: African Research